E1A Interacts with Two Opposing Transcriptional Pathways To Induce Quiescent Cells into S Phase - Sha, Jingfeng (American Society for Microbiology (ASM), 2010)
Despite data suggesting that the adenovirus E1A protein of 243 amino acids creates an S-phase environment in quiescent cells by overcoming the nucleosomal repression of E2F-regulated genes, the precise mechanisms underlying E1A's ability in this process have not yet been defined at the biochemical level. In this study, we show by kinetic analysis that E1A, as opposed to an E1A mutant failing to bind p130, can temporally eliminate corepressor complexes consisting of p130-E2F4 and HDAC1/2-mSin3B from the promoters of E2F-regulated genes in quiescent cells. Once the complexes are removed, the di-methylation of H3K9 at these promoters becomes dramatically diminished, and this in turn allows for the acetylation of H3K9/14 and the recruitment of activating E2F family members, which is then followed by the transcriptional activity of the E2F-regulated genes. Remarkably, although an E1A mutant that can no longer bind to a histone acetyltransferase (PCAF) is as capable as wild-type E1A in eliminating corepressor complexes and methyl groups from the promoters of these genes, it cannot mediate the acetylation of H3K9/14 or induce their transcription. These findings suggest that corepressors as well as coactivators are acted upon by E1A to derepress E2F-regulated genes in quiescent cells. Thus, our results highlight for the first time a functional relationship between E1A and two transcriptional pathways of differing functions for transitioning cells out of quiescence and into S phase.